Early childhood teachers' beliefs and experiences of identification and referral for early intervention services in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Baxter, Stacey (Massey University, 2017)
This research addresses a gap in the literature related to the role of early childhood teachers in the identification and referral of children for specialist early intervention, particularly in the Aotearoa New Zealand context. Extending on the prior work of Aspden (2003), this replicative study explored early childhood teachers’ experiences, attitudes and beliefs regarding the identification of children’s additional needs and subsequent referral for specialist early intervention. Two research questions framed this study: (1) what are early childhood teachers’ experiences related to identification and referral? and; (2) what factors, attitudes and beliefs influence early childhood teachers’ identification and referral practices? Seventy-eight early childhood teachers participated in an online survey. Key findings suggested that teachers’ identification and referral confidence was strongly influenced by a complex set of personal and external factors that included concerns around parental reaction and the adequacy of service provisions. Teachers reported low overall levels of confidence in specialist service provisions, creating a potential access barrier for children with additional needs. The findings support the ongoing need for teacher consultation in terms of current and future changes to the systems around specialist early intervention as well as enhanced professional support and development that targets teachers need for knowledge of and connection with specialist agencies.
Keywords: Learning disabilities; Diagnosis; Children with disabilities; Education (Early childhood); Problem children; Early childhood teachers; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education